TINJAUAN ATAS PROSEDUR PERJALANAN DINAS BAGIAN KEUANGAN PADA BADAN PENYULUHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA PERTANIAN KEMENTERIAN PERTANIAN INDONESIA - Putra Auliyya Birra, - (2018)
This PKL activity aims to develop the ability of students, to know how much the application of the theory that has been given in the classroom with the practices that have occurred, and so that they can measure the quality of themselves in the world of work. This street vendor was held for 1 month at the Indonesian Ministry of Agriculture. During Field Work Practices placed in the Secretariat and Finance Section of the PPSDMP Agency (Extension and Agricultural Human Resource Development). In carrying out Office Travel activities, it is necessary to develop a procedure as a basis for carrying out its activities. The procedure is the rule steps that must be obeyed by each unit in order to smooth the flow of information in the field. Official Travel Procedures are required for operating activities outlining the procedures for making Employee Service Travel Orders that will carry out official trips outside the area. Presidential Decree of the Republic of Indonesia Number 42 of 2002 dated June 28, 2002 concerning Guidelines for Implementing the State Revenue and Expenditure Budget s.t.d.d by the Regulation of the Minister of Finance of the Republic of Indonesia in conducting Official Travel activities. After carrying out the Field Work Practice Activities, it can be concluded that the Field Work Practice is very useful because it can add experience and knowledge about the procedure of business debt to a company. So that it can be used as a provision to enter the real world of work in the future.